Surface streamer propagations on an alumina bead: experimental observation and numerical modeling. (29th January 2018) - Kang, Woo Seok; Kim, Hyun-Ha; Teramoto, Yoshiyuki; Ogata, Atsushi; Lee, Jin Young; Kim, Dae-Woong; Hur, Min; Song, Young-Hoon
Abstract: A surface streamer in a simplified packed-bed reactor has been studied both experimentally (through time-resolved ICCD imaging) and theoretically (through two-dimensional numerical modeling). The propagation of streamers on an alumina spherical bead without catalytic coating shows three distinct phases—the generation and propagation of a primary streamer (PS) with a moderate velocity and electric field, fast PS acceleration with an enhanced electric field, and slow secondary streamer (SS) propagation. The velocity of the streamer is less than that of propagation in a gaseous media. The electric field and velocity at the streamer front are maximized when a PS propagates during the interval from the midpoint of the bead to the bottom electrode. The SS exhibits a much lower velocity and electric field compared with the PS. The PS velocity is affected by an external applied voltage, especially when it approaches the ground electrode. However, that of the SS remains constant regardless of the voltage change. The simulation shows that the PS exhibits a high electric field mainly created by the space charge induced by electrons, whereas the SS relies on ion movement with electron decay in a charge-filled thin streamer body.